Pemanfaatan Algoritma K-Means dalam Klasterisasi Gempa Sulawesi - Gunawan, Wawan; Wibowo, Arief (LPPM, 2024)
Indonesia is a region that frequently experiences earthquakes, especially in the Sulawesi area which has significant active faults. Sulawesi is an area that has quite high seismic intensity, and there are several active faults which are earthquake source zones. This study uses M-Means with a total of 9,710 records starting from 2019-2023 and the attributes consist of event_id, date_time, latitude, longitude, magnitude, mag_type, depth_km, phase_count, azimuth_gap, location, agencydengan. This data processing compares magnitude and depth consisting of 3 clusters, namely 51-132 Km depth with a total of 1,311, 3-50 Km depth with a total of 7,527, 133-300 Km depth with a total of 872, while the process with magnitude, depth and azimuth gap attributes consists of 4 clusters with each cluster respectively 3,957, 1,546, 1,458, and 2,749. By using a different set of input features, this research identifies that the results from 3 clusters or 4 clusters indicate that the province of South Sumatra shows a high level of earthquake proneness and frequent frequency in all clusters with the epicenter of the earthquake being in the Maluku Sea, between South Sulawesi with Southeast Sulawesi, as well as the province of Gorontalo. Based on the results obtained, there is a need for early prevention related to disasters, especially earthquakes that occurred on the island of Sumatra based on earth faults that run through the island..